The Cultural Perspective Of Filipino In Times Of Pandemic - Froilan D Mobo; Ana Liza R. Garcia; Abdul Rahmat (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Most Filipinos have different cultural perspective in times of Pandemic because they have their own believes. A good example is they are well known in terms of “Mamaya na System” for example in terms of the vaccination program here in the Philippines they will just follow if the government and the private entity will be requiring the vaccination ID Card anytime they have visited any places in the Philippines. The research suggested that to avoid this kind of situation occurs specially in this time of a pandemic. It is highly suggested implement stricter policies per places for example requiring them to wear Vaccination card at all time as part of the new Normal.